CROATIAN EXPERIENCE IN THE PROTECTION OF OWN HEROES - Storubliov, O. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article describes the experience of the formation of value orientations and public consciousness among the population and soldiers of Croatia, a country that gained and defended its independence from armed aggression in the 20th century. The activities of public authorities of the Republic of Croatia on increasing the prestige of military service, restoring and introducing national-historical and military traditions in the armed forces were analyzed. It reveals the structure of social protection and rehabilitation of servicemen of the armed forces of Croatia and the position of the country's military-political leadership in this direction. The versatile political and economic, cultural and humanitarian cooperation of Ukraine and Croatia, international relations with NATO were considered. The multi-vector procedure for the provision of psychological, medical, material rehabilitation and state guarantees for servicemen and reservists is disclosed in detail. The features of the Croatian national character, Croatian culture, observance of language etiquette, respect for the traditions and customs of older generations were scrutinized. Great importance is attached to the promotion of military service and the military professional guidance of the country's youth. One of the main tasks was to study the experience of the Ministry of Defense of the Republic of Croatia in the field of social protection of defenders. New for Ukraine is the experience of developing voluntary national defense in Croatia, which goal is to maximize the use of the resources of the whole society, especially civil society organizations, in the interests of increasing the state's defense capability.
Keywords: prestige of military service, armed forces, social protection